Mesenchymal stromal cells as rescue therapy in biologic-refractory psoriasis: insights from a case series - Lwin, Su M.; Solanky, Shane; Scottà, Cristiano; Giacomini, Chiara; Azrielant, Shir; Tosi, Isabella; Al-Haddabi, Atheer; Duarte-Williamson, Emelia; Dawe, Hannah; Walsh, Sarah; McGrath, John A.; Lombardi, Giovanna; et al. (Frontiers in Immunology, 2025)
Cytokine-targeted biologics have revolutionized the management of moderate-to-severe psoriasis; however, all available therapies have failed a growing number of patients. Mesenchymal stromal cells (MSCs), with their immunomodulatory properties, offer a novel therapeutic option. Here, we report the cases of three adult female patients with long-standing, severe plaque psoriasis who were refractory to multiple biologic therapies, and were consequently treated with two intravenous infusions of allogeneic umbilical cord-derived MSCs (UC-MSCs; 1.96 – 3.00 × 106 cells/kg) 1 week (W) apart. Two patients received UC-MSCs as monotherapy; one received them alongside etanercept. Upon relapse, two patients resumed their last failed biologic at W9, while one switched to a new biologic at W24. UC-MSCs were well-tolerated and yielded variable clinical benefits. The best responder to MSCs experienced an 87% reduction in the Psoriasis Area and Severity Index (PASI 87) by W4. Two patients showed improved responses to previously failed biologics (absolute PASI of 0–2), sustained for over 2 years following reinitiation. Multi-parameter flow cytometry revealed increased frequencies of CD4+ and CD8+ skin-homing (CLA+CD103−) and skin-recirculating (CLA+CD103+) memory T cells, CD25HiCD127LoFoxP3+ regulatory T cells, and non-classical (CD14LoCD16+) monocytes, associated with clinical improvements. These findings suggest that UC-MSCs may potentially provide direct benefits for biologic-refractory psoriasis and restore responsiveness to previously ineffective biologics, possibly by resetting the immune response. Further investigation in larger cohorts is warranted.